Protocol for a cohort comparison treatment study evaluating the efficacy of a dimensional adaptation of GPM (GPM-extended) compared to a classic outpatient GPM treatment for patient fulfilling criteria for BPD: the EPSYLIA project - Blay, Martin; Benmakhlouf, Inès; Zenou, Marion; Amate, Mélissa; Uludag-Martin, Arjin; Chevrier, François; Pomey, Marie-Laure; Brisebarre, Marie; Lebourleux, Paul; Lopepe, Oyhana; Cacouault, Julie; Lagadec, Saioa; et al. (Frontiers in Psychiatry, 2026)
Personality disorders (PD) are common and debilitating psychiatric conditions, often characterized by severe interpersonal and self-dysfunction. Borderline personality disorder (BPD) is the most studied PD, with treatments like Good Psychiatric Management (GPM) demonstrating effectiveness. To address the current state of the personality disorder field, where most evidence-based treatments have been developed using a categorical approach, while the most empirically supported approach is the dimensional one, we developed an adaptation of GPM (GPM-extended) integrating concepts of dimensional personality dysfunction into an established therapeutic framework. This prospective “here-there” study will compare GPM-extended with standard GPM in two outpatient facilities. This methodological choice is due to organizational and institutional limitations. Participants (≥18 years) meeting BPD criteria per the SCID-II will be included. The GPM-extended group incorporates a dimensional diagnostic framework focusing on three personality dilemmas (rejection/abandonment fears, self-esteem dysregulation, and perfection/control issues), with tailored psychoeducation and treatment priorities. The standard GPM group will follow the validated GPM protocol, emphasizing interpersonal hypersensitivity and standard psychoeducation. Both groups will receive weekly individual therapy and group interventions for one year. Between-group differences at 1-year follow-up will be assessed using multiple regression models adjusted for baseline scores. The primary outcome is the change in BPD symptom severity (ZAN-BPD). Secondary outcomes include personality functioning, traits, and various clinical dimensions such as impulsivity, emotional regulation, and social functioning. All patients having initiated the program and having initial data will be included in the analysis, with multiple imputations for missing data and sensitivity analyses planned. Altogether, this study seeks to evaluate the feasibility and efficacy of integrating dimensionality into GPM, offering a pragmatic pathway to improve PD treatment and bridging gaps between evidence-based conceptualizations and treatments of PD.Clinical trial registrationClinicalTrials.gov, identifier NCT06913738.